Proportionate algorithms for two-microphone active feedback cancellation - Albu, F.; Nakagawa, C.; Nordholm, Sven (IEEE, 2015)
In this paper we propose the use of the proportionate principle in order to improve the convergence characteristics of the two microphone method for acoustic feedback cancellation in hearing aids. The reason of using proportionate algorithms is to exploit the sparseness of the adaptive filter coefficients in the transform domain. The convergence improvement can be achieved for both speech and music signals at a moderate increase of the numerical complexity over that of a previous solution in the transform domain.